Association of increased body mass index and the presence of urinary tract infection in primigravidae - Tornel Miguel, Kenia (2023)
Introduction: The nutritional status of women before and during pregnancy is oneof the determinants of the risk of maternal morbidity and mortality. Objective:To determine the relationship between the increase in body mass index and thepresence of urinary tract infection in primigravidae. Methods: Case-control study inprimigravidae records. We studied sociodemographic variables (age, schooling, lifeas a couple and occupation), obstetric conditions (obstetric risk, weeks of beginningof prenatal control, weeks of pregnancy resolution and number of prenatal visits),anthropometry at the beginning and end of pregnancy (weight, height, body massindex and nutritional condition -underweight, normal weight, overweight andobesity-, weight gain and body mass index gain), and modification of nutritionalcondition at the beginning and end of pregnancy. Statistical analysis was performedwith percentages, averages, confidence intervals for averages, Chi2 test, odds ratio,confidence intervals for odds ratio, simple linear regression, and projection of eventoccurrence. Results: When the increase in body mass index was 5 kg/m2, the meanurinary tract infection corresponded to 1.62 and, if the increase in body mass indexwas 10 kg/m2, the mean urinary tract infection was 2.3. Conclusion: In our study, thegreater the increase in body mass index during pregnancy of the primigravida, thegreater her probability of presenting urinary tract infection.